Buddhist philosophy : a historical analysis - Kalupahana, David J., 1933- (Book collections on Project MUSE., 1976)
"This introduction to Buddhism examines its basic philosophical teachins and historical development, setting forth complex and significant ideas in a straightforward and simple style that is easily accessible to the student. The author's orientation is philosophical, rather than religious or sociological. This approach is both the uniqueness and the strength of the work"--Back cover